Country Life in South Africa with which is incorporated "The African Architect" - (:unkn) unknown (Institutes of South African Architects and the Chapter of South African Quantity Surveyors, 1915)
Country Life in South Africa with which is incorporated "The African Architect"
Journal of the Transvaal, Natal and Orange Free State Provincial Institutes of South African Architects and the Chapter of South African Quantity Surveyors
Journals
Keywords: South African Architectural History